2000
DOI: 10.1287/mnsc.46.4.563.12061
|View full text |Cite
|
Sign up to set email alerts
|

Frictionless Commerce? A Comparison of Internet and Conventional Retailers

Abstract: T here have been many claims that the Internet represents a new nearly "frictionless market." Our research empirically analyzes the characteristics of the Internet as a channel for two categories of homogeneous products-books and CDs. Using a data set of over 8,500 price observations collected over a period of 15 months, we compare pricing behavior at 41 Internet and conventional retail outlets.We find that prices on the Internet are 9 -16% lower than prices in conventional outlets, depending on whether taxes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
1,227
12
24

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,951 publications
(1,359 citation statements)
references
References 23 publications
54
1,227
12
24
Order By: Relevance
“…Some studies have found that online price dispersion is higher than offline price dispersion (Ancarani & Shankar, 2004;Brynjolfsson & Smith, 2000;Clay et al, 2002); others have found that offline price dispersion is higher (Brown & Goolsbee, 2002;Brynjolfsson & Smith, 2000); and still others have found no significant difference between online and offline price dispersion (Scholten & Smith, 2002). Moreover, as many sellers offer both online and offline retailing, researchers are motivated to explore how multichannel retailing influences price dispersion.…”
Section: Price Dispersionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have found that online price dispersion is higher than offline price dispersion (Ancarani & Shankar, 2004;Brynjolfsson & Smith, 2000;Clay et al, 2002); others have found that offline price dispersion is higher (Brown & Goolsbee, 2002;Brynjolfsson & Smith, 2000); and still others have found no significant difference between online and offline price dispersion (Scholten & Smith, 2002). Moreover, as many sellers offer both online and offline retailing, researchers are motivated to explore how multichannel retailing influences price dispersion.…”
Section: Price Dispersionmentioning
confidence: 99%
“…Motivated by previous studies on price dispersion (Brynjolfsson & Smith, 2000;Kim, et al, 2012;Lu et al, 2007), we select books and CDs as low-touch goods as their characteristics are more identical and stable. For high-touch products, we choose cell phones and clothes as their features (e.g., the sensitivity of screen) cannot be thoroughly known before purchase.…”
Section: Selection Of Product Categoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…This aimed to understand the world of the board members and how the boards on which they served dealt with IT. Since it has been observed that the perceived risks of electronic commerce are major impediments to the adoption of electronic commerce systems (Brynjolfsson andSmith 2000, Ernst andYoung 2000), it was decided to use this as a focus. The level of interest in electronic commerce in the business community generally added interest to the potential research subjects.…”
Section: It Governance Examinedmentioning
confidence: 99%